Peran Aset Berwujud, Ungkitan Finansial, Likuiditas, dan Laju Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Alifa Putri Nugraheni; Shinta Permata Sari (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Firm value is a reflection of a company's performance and success in attracting investor confidence and demonstrating future growth prospects. This study aims to analyze the effect of tangible assets, financial leverage, liquidity, and company growth rate on firm value in the basic materials sector listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. This study is a quantitative method using secondary data from companies' annual financial reports. The sample is determined using purposive sampling and consisted of 84 companies with a total of 234 observations after removing outliers. Data analysis is performed using multiple linear regression with the Stata version 18 program. The results show that Financial Leverage proxied by Debt to Equity Ratio and Total Asset Growth have an effect on firm value, which means that an optimal funding structure and good asset growth provide a positive signal to investors regarding the company's future prospects. Meanwhile, Tangible Assets and Liquidity proxied by Current Ratio have no effect on firm value, because the amount of tangible assets and liquidity levels do not necessarily reflect performance efficiency or the ability to generate profits that are attractive to investors. These findings indicate that financing decisions and asset growth are the main factors considered by investors in assessing the performance of companies in the basic materials sector.